Cultural Differences in Interpersonal Emotion Regulation - Liddell, Belinda J.; Williams, Emma N. (Frontiers in Psychology, 2019)
Cultural differences exist in the use of emotion regulation (ER) strategies, but the focus to date has been on intrapersonal ER strategies such as cognitive reappraisal. An emerging literature highlights the importance of interpersonal ER, which utilizes social cues to facilitate the regulation of emotional states. In cultures that place high value on social interconnectedness as integral to their collectivistic self-construal, including East Asian cultures, interpersonal ER strategies may be particularly effective in reducing negative affect but this has not been previously tested. In this study, two groups comprising East Asian (n = 48) and Western European (n = 38) participants were randomly assigned to receive a priming narration depicting the use of either interpersonal (e.g. social modelling, perspective taking) or intrapersonal (e.g. cognitive reappraisal) ER strategies during a stressful experience. They were then instructed to utilize similar ER strategies in an emotion reactivity task during which they viewed high arousing negative pictorial stimuli while their heart rate (HR), heart rate variability (high frequency power – HF-HRV) and subjective affective states were measured. First we found that the East Asian group reported higher use of self-reported interpersonal ER strategies of social modelling and perspective taking in daily life. During the experimental interpersonal prime exposure, the East Asian group showed elevated HF-HRV (relative to baseline) compared to the Western European group, indicating more adaptive emotion regulation, but this pattern was not sustained during the reactivity or recovery phases. Instead, the East Asian group demonstrated increased HF-HRV and decreased HR across both prime conditions. The East Asian group also showed greater decreases in positive affect across the course of the experiment. Furthermore, individual differences in social modelling and individualism moderated the effect of the ER prime in the East Asian group, and main effects for perspective taking and reappraisal were observed in the Western European group. The findings support the notion that engaging in interpersonal ER strategies may be more beneficial for East Asian groups when immediately exposed to a stressful situation, as these strategies are congruent with cultural context and preferences, but our priming methodology may have limited the longer-term benefits.